RATIONALIZATION OF CALCIUM ANTAGONIST IN PREECLAMPSIA - Novianty, Novianty; Tanzil, Sutomo; Theodorus, Theodorus (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Preeclampsia is a hypertension condition after the 20th week of pregnancy with proteinuria. Eclampsia is a preeclampsia with convulsion and or coma. In Indonesia preeclampsia and eclampsia still one of the main causes of maternal and perinatal mortality. The aim of this study was to know the pattern of utilization of calcium antagonists in hypertension in pregnancy in Mohammad Hoesin Hospital. Drug utilization study has been done at medical records ward in November until December 2013. The population is medical records of hypertension in pregnancy patients at The Medical Record Installation of Obstetrics and Gynecology Department of Mohammad Hoesin Hospital from July until December 2012. The sample is 63 medical records which fulfill the inclusion criteria. The result is tabulated in percentage and presented descriptively. There were 63 pregnant women with hypertension. Hypertension in pregnant women aged between 33 till 37 years old (40%). Hypertension in pregnant women was found in first pregnancy (11.3%). Hypertension in pregnant women was hypertension stage two (68.2%). Calcium antagonists that mainly used were nifedipine and amlodipine. Nifedipine was given orally in 10 mg dose three times daily (100%). Amlodipine was given orally in 10 mg dose once a day (100%). The most frequent drug that was given at the same time with hypertension drugs is magnesium sulphate (89%). The use of calcium antagonists in hypertension in pregnancy at Obstetrics and Gynecology Department of Mohammad Hoesin Hospital has been rational